U.S. demography in transition. Issue 3 (3rd July 2022) - Merchant, Emily Klancher; Alexander, Carrie S.
Abstract: Demography, the social science of population studies, has changed dramatically over the past forty years, responding to a dual crisis of funding and moral legitimacy that hit the field in the mid-1970s. This article uses structural topic modeling in conjunction with the Oral History Project of the Population Association of America (PAA) to examine how demography survived the crisis. It finds that demographers turned to a new source of funding, the National Institutes of Health, shifted their research focus from overseas population growth to domestic socioeconomic inequality, and transformed the PAA from an interest group for people concerned about population problems to a professional association for academic demographers. These three shifts turned demography into the field it is today.